Energy Deposition of Intense Femtosecond Laser Pulses in Ar Clusters (Journal of Atomic and Molecular Sciences, 2013)
The transmission of femtosecond laser pulses in the Ar atomic-clusters is studied, and the absorption of the laser energy is calculated using a new theoretical model. Then the relevant physics parameters including the continuous winded range, the maximum penetration depth and the stopping time, have been calculated. Thus, we re-examine theoretically the possibility of this model.